Forensic analysis of P2P derived amphetamine synthesis impurities: identification and characterization of indene by‐products. Issue 3 (15th January 2016) - Power, John D.; Kavanagh, Pierce; McLaughlin, Gavin; Dowling, Geraldine; Barry, Michael; O'Brien, John; Talbot, Brian; Twamley, Brendan; Brandt, Simon D.
Abstract : 1‐Phenyl‐2‐propanone (P2P) is an internationally monitored precursor that has become increasingly difficult for illicit amphetamine producers to source, which means that alternative routes to its preparation have become increasingly important. One such approach includes the hydrolysis of alpha ‐phenylacetoacetonitrile (APAAN) with sulfuric acid. Previously, we reported the identification of 4, 6‐dimethyl‐3, 5‐diphenylpryid‐2‐one following implementation of hydrolysis conditions and it was proposed that this compound might serve as one route specific by‐product in the APAAN to P2P conversion. This study continued to explore the presence of impurities formed during this conversion and expanded also into a second route of P2P synthesis starting from alpha ‐methylstyrene (AMS). All P2P products underwent the Leuckart procedure to probe the presence of P2P‐related impurities that might have carried through to the final product. Two by‐products associated with the APAAN hydrolysis route to P2P were identified as 2, 3‐diacetyl‐2, 3‐diphenylsuccinonitrile (1 ) and 2‐methyl‐1‐phenyl‐1, 3‐dicarbonitrile‐1 H ‐indene (2 ), respectively. Two by‐products associated with the AMS route to P2P and subsequent Leuckart reaction were 1, 1, 3‐trimethyl‐3‐phenyl‐2, 3‐dihydro‐1 H ‐indene (3 ) and 1‐phenyl‐ N ‐(phenylethyl)propan‐2‐amine (4 ), respectively. The two indenes (2 and3 ) identified in synthesized amphetamine originating from P2P suggested that it might be possible to differentiate between the two synthetic routes regarding the use of APAAN and AMS. Furthermore, the association of these compounds with amphetamine production appears to have been reported for the first time. The presence of compounds1 – 4 in seized amphetamine samples and waste products could facilitate the suggestion whether APAAN or AMS were employed in the synthesis route to the P2P. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Compound 21‐Phenyl‐2‐propanone (P2P) is a widely used precursor for amphetamine‐based drugs and the search for additional sources of P2P continues to evolve. This investigation revealed the presence of indene by‐products in amphetamine that was prepared by the Leuckart route when either alpha ‐phenylacetoacetonitrile or alpha ‐methylstyrene were employed as the precursors to P2P. An unsymmetrical dimer was also formed as a by‐product in the Leuckart synthesis of P2P generated from alpha ‐methylstyrene.